Pengaruh Strategi Pembelajaran dan Motivasi Berprestasi Terhadap Hasil Belajar Siswa SMA - Tsamarul Hizbi; Sapiruddin Sapiruddin; Badrul Wajdi (Kappa Journal, 2021)
This study aims to determine; (1) The difference between the physics learning outcomes of high school students who were taught using inquiry strategies and those taught with group investigation, (2) The effect of the interaction between learning strategies and achievement motivation on learning outcomes of high school students, (3) Differences in learning outcomes of high school students who have motivation High achievers were taught with inquiry strategy with students who were taught by group investigation., (4) Differences in physics learning outcomes of high school students with low achievement motivation were taught using inquiry strategy with students who were taught with group investigation (1) There were differences in physics learning outcomes for high school students those who were taught with inquiry strategies with students who were taught with group investigation., (2) There was an interaction effect between learning strategies and achievement motivation on the learning outcomes of high school students., (3) There were differences in physics learning outcomes for high school students with high achievement motivation to be studied. show with the Inquiry strategy with students who were taught with group investigation., (4) There was no difference in the results of studying physics for high school students who had low achievement motivation learned by inquiry strategy with students who were taught with group investigation..